Experimental and Computational Studies on the Thermal Degradation of Nitroazidobenzenes. Issue 1 (7th November 2012) - Özkaramete, Elif; Şenocak, Nilgün; İnal, Kübra E.; Öz, Sevi; Svoboda, Ingrid; Atakol, Orhan
Abstract In this combined experimental and theoretical study the thermal degradation of 2‐nitroazidobenzene (I), 2, 4‐dinitroazidobenzene (II) and 2, 4, 6‐trinitroazidobenzene (III) to yield benzofuroxan (IV), 4‐nitrobenzofuroxan (V), and 4, 6‐dinitrobenzofuroxan (VI) were investigated by thermoanalytical (TG, DSC) and computational methods. In contrast, furoxan formation was not observed for 4‐nitroazidobenzene (VII) under heating due to the para position of the nitro group in the benzene ring. All compounds were characterized by elemental analysis, vibrational (IR) spectroscopy and mass spectrometry. The crystal structure of compound III was determined by single‐crystal X‐ray diffraction. DFT‐based structure optimizations and frequency analyses were performed at the B3LYP/cc‐pVDZ level of theory. The structural parameters of the fully optimized compound III showed very good agreement with the single‐crystal X‐ray data. The enthalpies of formation for compounds I, II, III, IV, V, and VI were calculated using the complete basis set (CBS‐4M) method of Petersson and co‐workers in order to obtain accurate energies. The enthalpies of degradation for compounds I, II, and III were obtained from calculated enthalpies of formation according to the Hess Law and were compared with the experimental values, which were available from DSC analysis and were found to be in very good agreement.